NFM-09. PRELIMINARY REPORT OF A MULTICENTER, PHASE 2 STUDY OF BEVACIZUMAB IN CHILDREN AND ADULTS WITH NEUROFIBROMATOSIS 2 AND PROGRESSIVE VESTIBULAR SCHWANNOMAS: AN NF CLINICAL TRIALS CONSORTIUM STUDY. Issue 2 (22nd June 2018) - Tonsgard, James; Ullrich, Nicole; Blakeley, Jaishri; Rosser, Tena; Packer, Roger; Korf, Bruce; Fisher, Michael; Cutter, Gary; Plotkin, Scott; Karajannis, Matthias; Allen, Jeffrey; Wade Clapp, D; et al.
Abstract: Profound hearing loss is common in patients with neurofibromatosis 2 (NF2) and vestibular schwannomas (VS). Bevacizumab treatment at 7.5 mg/kg every 3 weeks has been associated with hearing improvement and tumor shrinkage in 36% and 43% of patients, respectively. However, the optimal treatment dose and schedule are unknown. This multicenter, phase II, open-label study evaluated subjects (≥6 years old) with NF2 and progressive VS. Subjects received bevacizumab 10 mg/kg every 2 weeks during induction therapy (6 months), and 5 mg/kg every 3 weeks during maintenance therapy (18 months). Hearing response was defined as a significant increase in word recognition score above baseline. Radiographic response was defined as ≥20% decrease in tumor volume from baseline. The primary endpoint was hearing response rate in the target ear at 6 months. We enrolled 22 subjects (median age=23 years). The overall hearing and radiographic response rates were 41% (9/22) and 23% (5/22), respectively. In an unplanned post-hoc analysis, the hearing and radiographic response rates were 14% (1/7) and 0% in pediatric subjects ≤21 years, as compared with 53% (8/15) and 33% (5/15) in adult subjects. Bevacizumab was well tolerated. Adverse events included hypertension, proteinuria, arthralgias, AST/bilirubin elevation, delayed wound healing, fatigue, and irregular menstruation. 11/13 women with elevated FSH underwent evaluation for premature ovarian insufficiency. All continued treatment with bevacizumab. Bevacizumab treatment at 10 mg/kg every 2 weeks is associated with hearing and radiographic response rates comparable to previous studies using lower doses. Pediatric subjects appear to benefit less than adults during bevacizumab treatment.